A versatile approach to determine instantaneous co-activation: Development, implementation and comparison to existing measures. Issue 11 (18th August 2018) - Viggiani, Daniel; Barrett, Jeff M; Fewster, Kayla M; Callaghan, Jack
Abstract: An adaptable method of computing muscle co-activity is presented. Instantaneous muscle activities from multiple muscles are reduced into commonality and activity level dimensions. Both dimensions are weighted independently and combined into a co-activation measure, Φ. Myoelectric data from relaxed and braced simulated rear vehicle impacts were used to compare Φ to two existing co-activity measures in muscle pair and multi-muscle cases, Φ showed greater sensitivity in the muscle pair case and could better discriminate the relaxed and braced conditions in the multi-muscle case than previous measures. The flexibility of Φ allowed tailoring to reflect the current purpose.